Strategi Pengajaran Dosen Dan Pengalaman Pembelajaran Mahasiswa Dalam Matematika Teknik Di Polytechnic Kuching Sarawak Malaysia - Leh, Ling Ying (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2013)
Teaching and learning approaches practiced by educators today mustÂ be different to suit the contents and time. Lecturers-teaching focused onÂ student-centered teaching should be encouraged and emphasized as highlyÂ active student involvement is required during the process of teaching andÂ learning. Active student involvement will form the interest of students toÂ explore knowledge. The purpose of this study is to get the studentsâ€™ perceptionÂ of the lecturersâ€™ teaching and studentsâ€™ learning experiences. In this study,the lecturersâ€™ teaching aspect highlighted is composed of a lecturer-centeredÂ teaching methods and student-centered teaching and learning experienceÂ aspects is in relation to active learning and passive learning. This studyÂ involved a total of 169 respondents among 2nd semester engineering studentsÂ of diploma program who are studying in Engineering Mathematics 2 atÂ Polytechnic Kuching Sarawak. These samples were identifid throughÂ stratifid random sampling method to answer a questionnaire about thelecturersâ€™ teaching and students learning experiences. The instrumentÂ used was a structured questionnaire which containing 20 items. The dataÂ obtained were analyzed using descriptive statistics; i.e. mean, percentageÂ and standard deviation. Through this study, the overall mean value obtainedÂ for lecturer-centered teaching methods and student-centered teachingÂ methods are respectively 4.08 and 3.81. While the overall mean for activeÂ learning and passive learning is respectively 3.65 and 4.04. In this regard,Â the role of the lecturers who teach should not be underestimated becauseÂ the majority of students still consider lecturer as a source of knowledgeÂ and â€œguardianâ€ of them.Keywords: Active learning, Student-centered teaching